Heat transfer in multi-phase materials - Ochsner, Andreas; Murch, Graeme E.; SpringerLink (Online service). (Berlin London Springer, 2011)
This book provides a profound understanding, which physical processes and mechanisms cause the heat transfer in composite and cellular materials. It shows models for all important classes of composite materials and introduces into the latest advances. In three parts, the book covers composite materials (Part I), porous and cellular materials (Part II) and the appearance of a conjoint solid phase and fluid aggregate (Part III).
Part A: Composite materials -- Continuum modeling of diffusive transport in inhomogeneous solids -- Thermal residual stresses on aluminium matrix composites -- Heat conduction in two-phase composite materials with three-dimensional microstructures and interfacial thermal resistance -- Heat transfer through thin imperfect interfaces -- Part B: Porous and cellular materials -- Heat transfer in metal foams -- Heat transfer in graphitic foams -- Heat transfer of polypropylene foams -- Polymer composites filled with inorganic hollow micro-spheres -- Radiative properties of two phase materials -- Predictions of effective thermal conductivity of complex materials -- Lattice Monte Carlo analysis of thermal diffusion in multi-phase materials -- Optimization of a unit periodic cell in lattice block materials aiming at thermo-mechanical applications -- Part C: Consideration of a fluid -- Thermal instabilities in a fluid saturated porous medium -- The modelling of local thermal non-equilibrium processes in porous media -- High porosity cellular material: morphology, boiling & conjugate heat transfer -- A bio-inspired capillary convection with encapsulated phase-change particles.
Electronic reproduction.
Keywords: Composite materials; Heat -- Transmission; Electronic books